Aktivitas pada Rumah Adat Tinggi sebagai Cerminan Identitas Nilai Sosial dan Budaya Masyarakat Indragiri Hulu - Rizki Gilang Ramadhan; Laila Fitriah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
This study aims to describe and analyze the activities taking place in the Rumah Adat Tinggi of Rengat as a reflection of the social and cultural identity of the Indragiri Hulu community. The research is motivated by the functional shift of traditional houses amid modernization, which threatens the continuity of local wisdom. This study employs a qualitative descriptive method. Data were collected through field observations, interviews with cultural figures and caretakers, and documentation of cultural events held in the traditional house. The findings indicate that the Rumah Adat Tinggi serves not only as a historical heritage but also as a social and cultural center for the community. Activities within it embody values such as mutual cooperation, deliberation, respect for ancestors, and cultural education for the younger generation. From the perspective of functionalism, the traditional house operates as a social system that maintains societal balance through social, cultural, and integrative functions. This research emphasizes the importance of revitalizing the Rumah Adat Tinggi to ensure its continued role as a living space for cultural transmission amid globalization.